Focal localization of the NHE-1 isoform of the Na+/H+ antiport: assessment of effects on intracellular pH. - Grinstein, S (1993)
Na+/H+ exchange (antiport) is a major pathway for the regulation of intracellular pH. Antiport activity is stimulated when suspended cells adhere to the substratum. In this report, immunofluorescence was used to study the subcellular localization of the ubiquitous NHE-1 isoform of the antiport. NHE-1 was not distributed homogeneously on the surface of the cells. Instead, antiports were found to accumulate along the border of lamellipodia and near the edge of finer processes. Dual immunofluorescence experiments demonstrated that vinculin, talin and F-actin are concentrated at sites of NHE-1 accumulation. A mutated construct of NHE-1 lacking residues 566-635 of the cytosolic domain also accumulated near marginal lamellae. In contrast, the focal distribution observed in adherent cells was not detectable in cells grown in suspension. Fluorescence ratio imaging was used to define the functional consequences of focal accumulation of NHE-1. In the steady state, the pH was virtually identical throughout the cytosol. Moreover, no pH gradients were found to develop when cells recovered from an acid load by activation of Na+/H+ exchange. This is probably because of the presence of high concentrations of mobile buffers in the cytosol. The focal accumulation of antiporters near the cell margins may be involved in stimulation by adherence and/or generation of local osmotic gradients.